Rebalancing in Japan : The Role of Private Consumption - Tokuoka, Kiichi (IMF Working Papers; Working Paper ;, 2010)
Boosting growth through rebalancing is critical for addressing pressures from Japan's aging population. This paper focuses on one important untapped source of growth - private consumption, and argues that the key to reviving consumption is boosting household disposable income through higher wages, especially in services, and higher property income. The paper also suggests that the impact of higher property income on consumption could be potentially large.